A simple HPLC method for the determination of halcinonide in lipid nanoparticles: development, validation, encapsulation efficiency, and in vitro drug permeation - Clarissa Elize Lopes; Gisele Langoski; Traudi Klein; Priscileila Colerato Ferrari; Paulo Vitor Farago (Universidade de São Paulo, 2017)
ABSTRACT Halcinonide is a high-potency topical glucocorticoid used for skin inflammation treatments that presents toxic systemic effects. A simple and quick analytical method to quantify the amount of halcinonide encapsulated into lipid nanoparticles, such as polymeric lipid-core nanoparticles and solid lipid nanoparticles, was developed and validated regarding the drug's encapsulation efficiency and in vitro permeation. The development and validation of the analytical method were carried out using the high performance liquid chromatography with the UV detection at 239 nm. The validation parameters were specificity, linearity, precision and accuracy, limits of detection and quantitation, and robustness. The method presented an isocratic flow rate of 1.0 mL.min-1, a mobile phase methanol:water (85:15 v/v), and a retention time of 4.21 min. The method was validated according to international and national regulations. The halcinonide encapsulation efficiency in nanoparticles was greater than 99% and the in vitro drug permeation study showed that less than 9% of the drug permeated through the membrane, indicating a nanoparticle reservoir effect, which can reduce the halcinonide's toxic systemic effects. These studies demonstrated the applicability of the developed and validated analytical method to quantify halcinonide in lipid nanoparticles.